Relationship marketing through the prism of customer loyalty - Juozas Bivainis (Business: Theory and Practice, 2011)
The paper sistemically analyzes two complex phenomena relevant to practice and science – mixture of relationship marketing and customer loyalty. The following fundamental aspects of these phenomena were analyzed: the historical context of relationship marketing and customer loyalty, content of relationship marketing at strategic and tactical levels, the most popular features of relationship marketing strategies, specifics of loyalty status change, the place of customer loyalty programs in marketing chain. Based on the results of the analysis a method for measuring the effect of marketing tools on the status of customer loyalty was prepared, the method has an integrated innovative component that calculates the synergy effect of marketing tools. The method was tested in analytical modelling manner, the possibilities of its application were discussed.